2020
DOI: 10.1016/j.joule.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A Nonionic and Low-Entropic MA(MMA)nPbI3-Ink for Fast Crystallization of Perovskite Thin Films

Abstract: A nonionic ink has been developed to facilitate rapid crystallization of perovskite with high film quality including strong crystal orientation and carrier diffusion length that reaches the single-crystal level. Solar cells based on this ink show an invariant efficiency over 21% regardless of the device area ranging from 0.096 to 0.5 cm 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 62 publications
1
58
0
Order By: Relevance
“…[ 38 ] Prior studies have also revealed that in a HOIP perovskite system, varying the ratio of inorganic to organic precursor will lead to an obvious self‐doping behavior. [ 45 ] Building upon the prior self‐doping strategies [ 45,46 ] and our recent reports of nonionic HOIP ink, [ 47,48 ] here we have developed a p‐type self‐doped mixed‐halide perovskite, p‐MAPbI 2 Br. It should be noted that the fabrication method based upon nonionic HOIP ink enables the realization of perovskite film with high texturing (Lotgering factor of 0.89) and homogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 38 ] Prior studies have also revealed that in a HOIP perovskite system, varying the ratio of inorganic to organic precursor will lead to an obvious self‐doping behavior. [ 45 ] Building upon the prior self‐doping strategies [ 45,46 ] and our recent reports of nonionic HOIP ink, [ 47,48 ] here we have developed a p‐type self‐doped mixed‐halide perovskite, p‐MAPbI 2 Br. It should be noted that the fabrication method based upon nonionic HOIP ink enables the realization of perovskite film with high texturing (Lotgering factor of 0.89) and homogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the fabrication method based upon nonionic HOIP ink enables the realization of perovskite film with high texturing (Lotgering factor of 0.89) and homogeneity. [ 47 ] This is a result of self‐assembly of perovskite intermediate in the nonionic ink precursor solution, which has a highly ordered layered structure that facilitates crystallization and film assembly. [ 47,49 ] This method is also compatible with the layer‐by‐layer device fabrication process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With these in mind, researchers have made great efforts on solvent engineering of perovskite precursor solution to balance the control of the film‐forming process and the reduction of the toxicity of solution‐processed perovskite film. So far, the advanced strategies of solvent engineering could be categorized into two major types, including regulation of coordination ability of solvent system (e.g., mixing of solvents with high D N with those with low D N ) [ 80–89 ] and reducing the toxicity of precursor solution (e.g., alcoholic, aqueous, and ionic liquids (ILs)‐based solvent) ( Figure ). [ 90–97 ]…”
Section: Introductionmentioning
confidence: 99%